2015
DOI: 10.1111/tri.12524
|View full text |Cite
|
Sign up to set email alerts
|

High peak alanine aminotransferase determines extra risk for nonanastomotic biliary strictures after liver transplantation with donation after circulatory death

Abstract: SummaryOrthotopic liver transplantation (OLT) with donation after circulatory death (DCD) often leads to a higher first week peak alanine aminotransferase (ALT) and a higher rate of biliary nonanastomotic strictures (NAS) as compared to donation after brain death (DBD). This retrospective study was to evaluate whether an association exists between peak ALT and the development of NAS in OLT with livers from DBD (n = 399) or DCD (n = 97) from two transplantation centers. Optimal cutoff value of peak ALT for risk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
20
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 39 publications
1
20
1
Order By: Relevance
“…Higher postoperative transaminase levels in recipients who develop NAS, however, is in concordance with other studies. (35,36) This further supports the thought that injury, and not increased coagulation, is the leading factor in the pathophysiology of NAS.…”
Section: Discussionsupporting
confidence: 74%
“…Higher postoperative transaminase levels in recipients who develop NAS, however, is in concordance with other studies. (35,36) This further supports the thought that injury, and not increased coagulation, is the leading factor in the pathophysiology of NAS.…”
Section: Discussionsupporting
confidence: 74%
“…Interestingly, the incidence of NAS in pediatric DCD livers was considerably lower than that reported in adult DCD livers [19,2830]. Although it is widely accepted that NAS is the most relevant and prevalent complication of adult DCD livers, this study indicates that this is not the case for pediatric DCD livers.…”
Section: Discussioncontrasting
confidence: 62%
“…A recent study from the Netherlands reported on 97 DCD liver recipients with a median asystolic donor warm ischemia of 17 minutes and a donor age of 44 years. The incidence of nonanastomotic biliary strictures cumulated in this analysis to 31%, 38 with a strong correlation between the degree of initial reperfusion injury (peak ALT) and subsequent biliary injury. This observation underlines the importance of the initial ischemia-reperfusion injury before implantation, which, for example, can be prevented by machine perfusion techniques.…”
Section: Discussionmentioning
confidence: 89%